Acidic Water Oxidation on Quantum Dots of IrOx/Graphdiyne (Adv. Energy Mater. 32/2021). Issue 32 (26th August 2021) - Wang, Zhongqiang; Zheng, Zhiqiang; Xue, Yurui; He, Feng; Li, Yuliang
Abstract : Quantum Dots In article number 2101138, Yurui Xue, Feng He, Yuliang Li and co‐workers demonstrate controllable growth of iridium oxide quantum dots by exploiting the unique properties of graphdiyne. This provides an ideal system to control the preparation of small size, quantum dot catalysts, fully demonstrating the size and quantum effects of these catalysts in the catalytic process, and obtaining highly active and robust catalysts with excellent acidic water oxidation performance.